Assessment of the load-loading capacity of bolted joints during bolt bending and the combination of materials used - Kravchenko Georgy; Durov Dmitry; Kravchenko Konstantin; Linkov Nickolay (BIO Web of Conferences, 2024)
Abstract: based on the physical model of a hinged-bolt joint, which takes into account the possible bending of the bolt and, consequently, the real nature of the distribution of contact loads, the influence of the main design parameters of the joints on the distribution of loads between individual elements depending on the combination of their materials is analyzed. Dependencies for determining normal stresses in a given section of a connection element are presented, variants of the structural and technological design of typical hinge-bolt connections are analyzed according to the degree of influence of their geometric and material science features on the level of contact loads.